Supersonic business jet conceptual design in a multidisciplinary design analysis optimization environment - Sun, Yicheng; Smith, Howard (AIAA, 2018)
This paper introduces a multidisciplinary design analysis and optimization (MDAO) environment called GENUS, which has been developing in Cranfield University’s Aircraft Design Group. The GENUS aircraft design environment has the feature of modular, expandable, flexible, independent, sustainable, and performable. This paper discusses the application of this environment to supersonic business jets (SSBJs), which are regarded as the pioneer of the next generation of supersonic airliners. Methodologies appropriate to SSBJ are developed in the GENUS environment. Mach plane cross-sectional area is calculated based on the parametric geometry model. PANAIR is modified to do automated aerodynamic analysis. Drag coefficient is corrected by Harris wave drag calculation and form factor method. NASA EngineSim is integrated for engine modeling. Carlson simplified sonic boom prediction method has been used for sonic boom signature prediction. Results of the Cranfield E5 SSBJ are presented. Low-boom and low-drag SSBJ designs can be explored based on the framework.